Lung recruitment manoeuvre strategies in paediatric intensive care units across Europe - Elisa Poletto; Marco Daverio; Robert George Theodoor Blokpoel; Gloria Brigiari; Dario Gregori; Marti Pons-Odena; Alvise Tosoni; the Country Representatives Consortia Authorship with the endorsement of the ESPNIC Respiratory Failure Section; K. Elmira; G. Cortina; E. Duval; R. Kikas; et al. (ERJ Open Research)
Introduction In severe paediatric acute respiratory distress syndrome (PARDS) lung recruitment manoeuvres (LRMs) may be applied to improve oxygenation, but their application is still controversial. The aim of this survey is to report what the current practice is across European paediatric intensive care units (PICUs). Methods An online survey was distributed to PICUs in 19 European countries targeting paediatric intensivists, nurses and respiratory therapists. One reply per unit was allowed. Results 151 PICUs out of 276 (54.8%) responded. Of those, 75.9% have more than 300 admissions per year and 45.1% are extracorporeal membrane oxygenation (ECMO) centres. LRMs are employed in 78.9% of surveyed PICUs. Twenty-three out of 105 (21.9%) PICUs have a standardised protocol. LRMs are mainly performed by physicians (99%), supported by nurses (38.4%) and/or respiratory therapists (11.5%). The main reported contraindications are air leak (86.7%), haemodynamic instability (75.2%) and intracranial hypertension (63.8%). Staircase recruitment manoeuvres (SRMs) are the most commonly (69.5%) practiced LRMs, while sustained inflation is used in 44.8% of PICUs, alone or in addition to SRMs. The success of LRMs is measured through oxygenation improvement (oxygenation index or arterial oxygen tension/inspiratory oxygen fraction). Profound hypotension is the most reported complication (49.5%), while 35.2% did not report any complication. Lack of familiarity is the main obstacle to the application of LRMs (67.9%). Conclusions To our best knowledge this is the first survey providing an overview of current LRMs application among European PICUs. Practise is diverse among countries and PICUs. Further research is necessary to build stronger evidence to support a more standard application of LRMs.